Torulaspora delbrueckii Yeast Strains for Small-scale Chenin blanc and Pinotage Vinifications - van Breda, V.; Jolly, N.P.; Booyse, M.; van Wyk, J. (South African Journal of Enology and Viticulture, 2018)
Nine Torulaspora delbrueckii yeast strains, a commercial T. delbrueckii strain and a commercial Saccharomyces cerevisiae yeast strain were used in the production of small‑scale Chenin blanc and Pinotage vinifications. The fermentations were carried out at 15°C and 24°C respectively. Four T. delbrueckii yeasts were used as single inoculants, while the remainder were inoculated sequentially. The commercial S. cerevisiae yeast strains were added at zero, 24 and 48 hours after the T. delbrueckii strain. The wines were evaluated chemically and sensorially and the data was analysed statistically. The results for the white wine vinification trial showed that two T. delbrueckii treatments could produce novel wines, either on their own or as a component of co‑inoculated fermentations. These compared well with, and even exceeded, the quality of wine produced by the S. cerevisiae reference treatment regarding chemical composition and overall sensory quality. One T. delbrueckii strain showed its robustness by being re-isolated from the yeast lees at the end of fermentation. The red wine vinifications were less conclusive, and no distinctive T. delbrueckii “fingerprint” was observed in the chemical and sensory data, neither was a pattern observed regarding the different inoculation times.